An Advanced Preclinical Mouse Model for Acute Myeloid Leukemia Using Patients' Cells of Various Genetic Subgroups and In Vivo Bioluminescence Imaging - Vick, Binje; Rothenberg, Maja; Sandhöfer, Nadine; Carlet, Michela; Finkenzeller, Cornelia; Krupka, Christina; Grunert, Michaela; Trumpp, Andreas; Corbacioglu, Selim; Ebinger, Martin; André, Maya C.; Hiddemann, Wolfgang; et al. (PLOS ONE, 2015)
Acute myeloid leukemia (AML) is a clinically and molecularly heterogeneous disease with poor outcome. Adequate model systems are required for preclinical studies to improve understanding of AML biology and to develop novel, rational treatment approaches. Xenografts in immunodeficient mice allow performing functional studies on patient-derived AML cells. We have established an improved model system that integrates serial retransplantation of patient-derived xenograft (PDX) cells in mice, genetic manipulation by lentiviral transduction, and essential quality controls by immunophenotyping and targeted resequencing of driver genes. 17/29 samples showed primary engraftment, 10/17 samples could be retransplanted and some of them allowed virtually indefinite serial transplantation. 5/6 samples were successfully transduced using lentiviruses. Neither serial transplantation nor genetic engineering markedly altered sample characteristics analyzed. Transgene expression was stable in PDX AML cells. Example given, recombinant luciferase enabled bioluminescence in vivo imaging and highly sensitive and reliable disease monitoring; imaging visualized minimal disease at 1 PDX cell in 10000 mouse bone marrow cells and facilitated quantifying leukemia initiating cells. We conclude that serial expansion, genetic engineering and imaging represent valuable tools to improve the individualized xenograft mouse model of AML. Prospectively, these advancements enable repetitive, clinically relevant studies on AML biology and preclinical treatment trials on genetically defined and heterogeneous subgroups.